Batik Motifs From Mathematical Model Of Earthquake Waves And Kartini Reactor - Sugiyanto; Bariromah; M. Aly Akbar Hakim; Hamas Abdillah; Wida Yaska Andika Yusuf (Jurnal Ilmiah Matematika, 2023)
The batik motif from the mathematical model of earthquake waves and the Kartini Reactor is an innovation in the world of batik that combines elements of art and science. Earthquake waves are complex physical phenomena that occur as a result of the release of energy from earthquake sources that propagate through the layers of the earth in seismic form. The mathematical modeling used to understand the dynamics of wave propagation is partial differential equations and numerical simulation methods. In addition, this research highlights the role of Raktor Kartini, a nuclear reactor located in Yogyakarta, for the development of science and technology in Indonesia. In this research, the earthquake wave propagation pattern and the dynamics of the Kartini Reactor are translated into batik motifs, creating a visual representation of scientific concepts. This approach not only enriches the cultural heritage of batik, but also introduces science to the public. The philosophy of this motif emphasizes the balance between resilience and flexibility, reflecting how technological systems must adapt to dynamic environmental conditions.